Interferon-regulatory factor-1 (IRF1) regulates bevacizumab induced autophagy - Liang, Ji (Oncotarget, 2015)
PURPOSE: Antiangiogenic therapy is commonly being used for the treatment of glioblastoma. However, the benefits of angiogenesis inhibitors are typically transient and resistance often develops. Determining the mechanism of treatment failure of the VEGF monoclonal antibody bevacizumab for malignant glioma would provide insight into approaches to overcome therapeutic resistance. EXPERIMENTAL DESIGN: In this study, we evaluated the effects of bevacizumab on the autophagy of glioma cells and determined target genes involving in the regulation of bevacizumab-induced autophagy. RESULTS: We demonstrated that bevacizumab treatment increased expression of autophagy markers and autophagosome formation in cell culture experiments as well as in in vivo studies. Gene expression profile analysis performed on murine xenograft models of glioblastoma showed increased transcriptional levels of STAT1/IRF1 signaling in bevacizumab resistant tumors compared to control tumors. In vitro experiments showed that bevacizumab treatment increased IRF1 expression in a dose and time dependent manner, which was coincident with bevacizumab-mediated autophagy. Down regulation of IRF1 by shRNA blocked autophagy and increased AIF-dependent apoptosis in bevacizumab-treated glioma cells. Consistently, IRF1 depletion increased the efficacy of anti-VEGF therapy in a glioma xenograft model, which was due to less bevacizumab-promoted autophagy and increased apoptosis in tumors with down-regulated IRF1. CONCLUSIONS: These data suggest that IRF1 may regulate bevacizumab-induced autophagy, and may be one important mediator of glioblastoma resistant to bevacizumab.